PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARNING SEKOLAH DASAR NEGERI - Lestari, Winda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract A common problem in this research is whether the usage of the CTL model improve the narrative essay writing skills of student of class V state primary School South East Pontianak 09? The general objective in this study was to improve the skills of writing a narrative essay using the model of CTL in class V. This research uss descriptive mthod with the class action research and collaboration. The place of research taking place is in elementary school the country south. East Pontianak with subject 09 research i.e.class V of 32 people. Data collection techniques used i.e.observation with the pencematan document, namly sheets of observation and pencermatan document. The data collected was analyzed with a calculation of average and percentage. This research was conducted as much as II cycles with 2 times on each cycle. The research result obtained is the ability of teacher in designing learning cycle I by average score 3.28, cycle II increased to the average score 3.89. The result of the research capabilities of teachers implement pembelajaran on cycle I with an average score of 3,47 cycle II with an average score 3,91. The result of student learning on learning to write a narrative essay on cycle I mean namely 65,51 and cycle II average 73,79. The conclusions of the analysis of the data obtained, this shows that the penggunaan model can improve the skills of the CTL student in writing a narrative essay. Keywords: Peningkatan, karangan narasi, model Contextual Teaching and Learning Â Â